HACKING MACROS VIRUS USING OPEN SOURCE - Hari Suryantoro; Irwan Bastian. Skom. MMSi (Jurnal Sistem Informasi, 2001)
In general this paper aims to provide knowledge to computer users, especially usersof Microsoft Word application program, about Macro viruses (viruses that infect filedocuments). In this writing, the author tries to explain all the things about macroviruses, from the manufa cturing process of various versions of Macro virus, macromacrosused by macro viruses, Macro viruses in protecting themselves, the evils ofmacro viruses that can harm a computer user data , how to detect the presence ofvirus in a dukomen Macro and open source code viruses. Protection facilities inMicrosoft Word, the macro virus treatment and prevention must become a userwithout anti- virus, and viruses in a simple Macro.